2023
DOI: 10.1007/s10639-023-11617-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of software development course on programming self-efficacy

Abstract: Negative attitudes and perceptions on programming impair the effectiveness of learning programming skills. In this study the attitude related to programming, problem solving, and self-views on importance of IT/programming knowledge were assessed by pre- and post-test completed at the beginning and at the end of a software development course. The study was conducted using an online questionnaire and four different dimensions were measured by a survey consisting 23 items. The results show positive moderate assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Such advances in systems such as VR/AR and brain–computer interfaces may also benefit rehabilitation by increasing participant self-confidence and self-efficacy [ 81 , 82 ]. Previous studies have shown that incorporating “gamified” systems and computer/programming training into learning modules can improve self-efficacy more than standard instruction alone [ 83 , 84 ]; thus, it is likely that such systems could have a similar effect on self-efficacy during cognitive-motor rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Such advances in systems such as VR/AR and brain–computer interfaces may also benefit rehabilitation by increasing participant self-confidence and self-efficacy [ 81 , 82 ]. Previous studies have shown that incorporating “gamified” systems and computer/programming training into learning modules can improve self-efficacy more than standard instruction alone [ 83 , 84 ]; thus, it is likely that such systems could have a similar effect on self-efficacy during cognitive-motor rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this protocol will allow monitoring Mexican children who will use Smartick, so that a follow-up psychophysiological evaluation can be performed to show if the OML caused learning enhancement. Previous research has demonstrated that using learning technology helps to increase motivation and improves self-efficacy and self-confidence ( Kovari and Katona, 2023 ). This work could be applied in other Spanish-speaking countries that wish to evaluate AT for learning in children.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy may affect learners’ effectiveness in learning basic programming concepts (Kovari & Katona, 2023; Law et al, 2010; Ramalingam et al, 2004). If proper strategies are used to improve students’ self-efficacy, it may be more effective in fostering their basic programming concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have pointed out that programming beginners have difficulties with learning (Law et al, 2010; Ramalingam & Wiedenbeck, 2004), which may stem from their self-efficacy factor (Çoban et al, 2020; Kong et al, 2018; Tsai, 2019; Yukselturk & Altiok, 2017). Thus, the self-efficacy factor was examined in previous studies on general programming (Kong et al, 2018; Kovari & Katona, 2023) or block-based programming (Belland et al, 2022; Durak, 2018; Ma et al, 2021; Wei et al, 2021; Yukselturk & Altiok, 2017; Çoban et al, 2020). For example, in Durak’s (2018) study, students used Scratch to carry out digital story design activities in programming learning.…”
Section: Literature Reviewmentioning
confidence: 99%